Blunted ventral striatal responses to anticipated rewards foreshadow problematic drug use in novelty-seeking adolescents - Christian Büchel (Nature Portfolio, 2017)
Some adolescents seek novelty, but it is unknown whether the brain circuits underlying this behaviour can be used to predict later, problematic behaviour. Here, authors show that diminished ventral striatal and prefrontal activity in response to anticipated rewards at age 14 in these individuals predicts problematic drug use at age 16.